HIGH RISK CLIENTS evidence-based assessments and clinical tools to recognize and effectively respond to mental health crises;evidence-based. - BRASLER, PAUL (PESI PUBLISHING & MEDIA, 2019)
High Risk Clients provides a comprehensive and concise resource that you will turn to time after time to effectively intervene and keep clients safe.